1972
DOI: 10.1111/j.1432-1033.1972.tb01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Histone F1 with DNA in 0.15 M NaCl

Abstract: Aggregated complexes of histone F1 with DNA of different composition and origin were prepared by gradual dialysis from a high salt concentration to 0.15M NaCl. Analysis of the DNA composition both in the supernatant and in the precipitate showed that in equilibrium complexes in this medium, histone Fl selectively prefers sequences of native DNA rich in adenine and thymine. The mechanism of the selective binding is discussed.Study of complexes reconstituted from isolated DNA and from histone fractions represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

1972
1972
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 34 publications
(8 reference statements)
3
18
1
Order By: Relevance
“…The simplest explanation is that we enriched preferential binding sites since they are not present on all DNA fragments of 2 X 105 daltons. The melting temperature of the retained DNA was 50 lower (which corresponds to 12% more A + T) and reannealing of the DNA (Cot plot) indicated a lack of highly repetitive DNA fragments (G + Crich), in agreement with Sponar and Sormova (19).…”
Section: Resultssupporting
confidence: 81%
“…The simplest explanation is that we enriched preferential binding sites since they are not present on all DNA fragments of 2 X 105 daltons. The melting temperature of the retained DNA was 50 lower (which corresponds to 12% more A + T) and reannealing of the DNA (Cot plot) indicated a lack of highly repetitive DNA fragments (G + Crich), in agreement with Sponar and Sormova (19).…”
Section: Resultssupporting
confidence: 81%
“…4), however, and the finding of a similar transition of histone H1 complexes made with large DNA fragments (12) leads us to believe that histone H1 is also bound cooperatively on large fiber fragments and most likely also on native fibers at high ionic strength. The binding sites of histone H1 could be DNA sequences rich in A+T (20), because model studies showed a selective histone H1 interaction with DNA species of high A+T content (21).…”
Section: Discussionmentioning
confidence: 99%
“…Preparations of DNA, their isolation, fractionation, and characterization, as well as isolation and characterization of histone F1 are described elsewhere. 8 The complexes were prepared from isolated components (DNA and F1) dissolved at a given weight ratio in 1.5-3M NaCl by gradual dialysis down to 0.4M NaCl (4 hr), 0.3M NaCl (2 hr), and 0.15M NaCl (overnight) at 4°C. All solutions were buffered with 0.013M sodium phosphate (pH 6.8).…”
Section: Methodsmentioning
confidence: 99%